Pengaruh Role Stressor Terhadap Burnout dan Perbedaan Burnout Berdasarkan Gender: Studi Empiris pada Mahasiswa - - Lina; Budi Hartono Kusuma (Jurnal Akuntansi, 2018)
This study aims to provide empirical evidence about the positive effects of role stressors on burnout. Role stressor consists of role conflict, role ambiguity, and role overload. This study also wants to prove the difference level of burnout based on gender. The research data is the primary data that are obtained through the distribution of questionnaires to the respondents. The respondents were selected by using purposive sampling method. The specified criteria are as follows: last year students from undergradate accounting program at a private university in Tangerang. Hypothesis testing using multiple regression test and independent sample t test. The results revealed that role ambiguity and role overload have positive effect on burnout meanwhile role conflict has no effect on burnout. Differences in burnout based on gender can not be proven through the results of this study.Â Keywords: Role Stressor, Burnout, Gender